Inhibition of Histone Deacetylase 3 (HDAC3) Mediates Ischemic Preconditioning and Protects Cortical Neurons against Ischemia in Rats - Yang, Xiaoyu; Wu, Qimei; Zhang, Lei; Feng, Linyin (Frontiers in Molecular Neuroscience, 2016)
Brain ischemic preconditioning (PC) provides vital insights into the endogenous protection against stroke. Genomic and epigenetic responses to PC condition the brain into a state of ischemic tolerance. Notably, PC induces the elevation of histone acetylation, consistent with evidence that histone deacetylase (HDAC) inhibitors protect the brain from ischemic injury. However, less is known about the specific roles of HDACs in this process. HDAC3 has been implicated in several neurodegenerative conditions. Deletion of HDAC3 confers protection against neurotoxicity and neuronal injury. Here, we hypothesized that inhibition of HDAC3 may contribute to the neuronal survival elicited by PC. To address this notion, PC and transient middle cerebral artery occlusion (MCAO) were conducted in Sprague-Dawley rats. Additionally, primary cultured cortical neurons were used to identify the modulators and effectors of HDAC3 involved in PC. We found that nuclear localization of HDAC3 was significantly reduced following PC in vivo and in vitro. Treatment with the HDAC3-specific inhibitor, RGFP966, mimicked the neuroprotective effects of PC 24 h and 7 d after MCAO, causing a reduced infarct volume and less Fluoro-Jade C staining. Improved functional outcomes were observed in the neurological score and rotarod test. We further showed that attenuated recruitment of HDAC3 to promoter regions following PC potentiates transcriptional initiation of genes including Hspa1a, Bcl2l1, and Prdx2, which may underlie the mechanism of protection. In addition, PC-activated calpains were implicated in the cleavage of HDAC3. Pretreatment with calpeptin blockaded the attenuated nuclear distribution of HDAC3 and the protective effect of PC in vivo. Collectively, these results demonstrate that the inhibition of HDAC3 preconditions the brain against ischemic insults, indicating a new approach to evoke endogenous protection against stroke.